Complete chloroplast genome sequence and annotation of the Saccharum hybrid cultivar RB867515 - Vidigal, Pedro Marcus Pereira; Coelho, Alexandre Siqueira Guedes; Novaes, Evandro; Barbosa, Márcio Henrique Pereira; Peternelli, Luiz Alexandre (Genome Announcements, 2016)
Here, we present the chloroplast genome sequence of the Saccharum hybrid cultivar RB867515, the most planted sugarcane cultivar in Brazil.
Keywords: Chloroplast genome sequence; Saccharum hybrid; Cultivar RB867515